PERAN KESAMAAN PERILAKU DAN PERSEPSI RISIKO KESEHATAN TERHADAP PARA-SOCIAL INTERACTION DAN NIAT BELI MAKANAN SEHAT BERKELANJUTAN - Fanny Dwi Puspitasari; Purwanto; Fatchurrohman, Mochamad (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the relationship between healthy behavior similarity and health risk perception on para-social interaction (PSI) and the intention to purchase sustainable healthy food. Drawing upon the Health Belief Model (HBM), this research develops and validates a conceptual model linking healthy behavior similarity to PSI and purchase intention. A validated sample of 198 respondents was analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that (1) healthy behavior similarity is positively associated with PSI and consumers’ purchase intention; (2) perceived susceptibility and severity are also positively related to PSI and purchase intention. Lastly, PSI positively influences consumers’ intention to purchase. These findings highlight the effectiveness of digital celebrity endorsements in enhancing follower engagement and encouraging the purchase of health-related products.